1978
DOI: 10.1002/art.1780210502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the arthritis of mixed connective tissue disease

Abstract: Seventeen of 19 patients with mixed connective tissue disease (MCTD) had arthritis as a significant initial feature of their disease; 8 were given an initial diagnosis of rheumatoid arthritis (RA) and 4 received chrysotherapy. RA‐like hand deformities were present in 35% and contractures and/or persistent loss of joint motion in 47%. Joint radiographs showed abnormalities in 41% and included erosions and/or cysts in 30%. The arthritis of MCTD may be both erosive and deforming and this disease should be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
3
4

Year Published

1979
1979
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 18 publications
0
20
3
4
Order By: Relevance
“…[4][5][6][7][8][9] Since it was reported by Waaler in 1940 and Rose et al in 1948, RF has been widely used to diagnose RA. However, there has been a need for a substitute marker that is more reproducible, easy to use, and efficient for the diagnosis of RA because the specificity of RF is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] Since it was reported by Waaler in 1940 and Rose et al in 1948, RF has been widely used to diagnose RA. However, there has been a need for a substitute marker that is more reproducible, easy to use, and efficient for the diagnosis of RA because the specificity of RF is limited.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, subsequent studies on the clinical and radiographic manifestations of MCTD have shown that more than 30% of patients have developed erosive arthritis and joints like those seen in patients with rheumatoid arthritis (RA). [4][5][6][7][8][9] Therefore, it is widely accepted that RA is also part of the disease spectrum of this overlapping syndrome. [4][5][6][7][8][9] Recently, antibodies to cyclic citrullinated peptide (CCP) were reported as a novel serological marker for RA, with higher specificity than rheumatoid factor (RF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bony changes in the wrist have been documented in MCTD. 8 However, as far as we are aware, there are no reported cases of MCTD with spontaneous rupture of an extensor tendon in the wrist. In the present case, radiographic findings of the wrist showed changes in the radiocarpal joint and dorsal subluxation of the distal ulna.…”
Section: Discussionmentioning
confidence: 97%
“…In mixed connective tissue disease, complete ankylosis of the distal interphalangeal (8), metacarpophalangeal, proximal interphalangeal, radiocarpal (9), and hip joints (10) has been described. The absence of high antibody titers to extractable nuclear antigen and typical clinical features of mixed connective tissue disease excludes that diagnosis in this case.…”
mentioning
confidence: 99%